C5 conserved region of hydrophilic C-terminal part of Saccharomyces cerevisiae Nha1 antiporter determines its requirement of Erv14 COPII cargo receptor for plasma-membrane targeting - Papouskova, Klara; Moravcova, Michaela; Masrati, Gal; Ben-Tal, Nir; Sychrova, Hana; Zimmermannova, Olga (Molecular microbiology, 2021)
Erv14, a conserved cargo receptor of COPII vesicles, helps the proper trafficking of many but not all transporters to the yeast plasma membrane, for example, three out of five alkali-metal-cation transporters in Saccharomyces cerevisiae. Among them, the Nha1 cation/proton antiporter, which participates in cell cation and pH homeostasis, is a large membrane protein (985 aa) possessing a long hydrophilic C-terminus (552 aa) containing six conserved regions (C1-C6) with unknown function. A short Nha1 version, lacking almost the entire C-terminus, still binds to Erv14 but does not need it to be targeted to the plasma membrane. Comparing the localization and function of ScNha1 variants shortened at its C-terminus in cells with or without Erv14 reveals that only ScNha1 versions possessing the complete C5 region are dependent on Erv14. In addition, our broad evolutionary conservation analysis of fungal Na+ /H+ antiporters identified new conserved regions in their C-termini, and our experiments newly show C5 and other, so far unknown, regions of the C-terminus, to be involved in the functionality and substrate specificity of ScNha1. Taken together, our results reveal that also relatively small hydrophilic parts of some yeast membrane proteins underlie their need to interact with the Erv14 cargo receptor.
Keywords: buněčná membrána; Membrane Proteins; transport proteinů; Sodium; proteiny přenášející kationty; Cation Transport Proteins; Protein Transport; Erv14; Saccharomyces cerevisiae - proteiny; cargo receptor; antiportéry; Nha1; Antiporters; Saccharomyces cerevisiae Proteins; COPII; alkali-metal-cation homeostasis; Endoplasmic Reticulum; yeast; sodík; COP-Coated Vesicles; COP-vezikuly; Saccharomyces cerevisiae; membránové proteiny; endoplazmatické retikulum; Cell Membrane